A STUDY OF THE IMPACT OF CO-CURRICULAR ACTIVITIES ON SOCIAL SKILLS AND EMOTIONAL MATURITY OF STUDENTS STUDYING IN GOVERNMENT SCHOOLS – IN THE CONTEXT OF DURG DISTRICT, CHHATTISGARH - Jha, Pragya; Dewangan, Savita (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The objective of this study is to conduct a thorough evaluation of the impact of co-curricular activities on the social skills and emotional maturity of students studying in government schools in Durg District, Chhattisgarh. It has been established in the modern education system that co-curricular activities (such as sports, cultural activities, debates, science exhibitions, etc.) not only enhance academic achievement but also mature the social and emotional aspects of students' personalities. Adolescence, especially the age of 13–15 years, is crucial for this development, as it is during this stage that social identity, emotional balance, and self-confidence are formed. The study population consisted of 600 students from selected government and private schools in Durg district. For this research, 305 students (grades 9th to 12th, aged 13–15 years) from government schools were selected using stratified random sampling. The Social Skills Rating Scale (SSR) developed by Vishal Sood, Aarti Anand, and Suresh Kumar (2012) was used to measure social skills, and the Emotional Maturity Scale (EMS) by Tara Sabapathy (2017) was used to measure emotional maturity. The High School Adjustment Inventory (HSAI-SG) by A.K. Singh and A. Sen Gupta was also used throughout the research, but the analysis in this paper primarily focuses on SSR and EMS. Descriptive statistics (mean, standard deviation, percentage) and inferential statistics (t-tests and correlation analysis) were used for statistical analysis. The results revealed no significant difference in social skills (t=0.864, p=0.388) and emotional maturity (t=0.785, p=0.433) between male and female students in government schools. Furthermore, a moderate positive correlation (r=0.342, p<0.01) was found between social skills and emotional maturity. The main finding of the study is that the impact of co-curricular activities is equally evident across gender in government schools. This finding is important not only for educational policymakers but also for teachers and school administrators to ensure that co-curricular activities are implemented in an inclusive and balanced manner that equally promotes students' social and emotional development.